Laparoscopic myomectomy vs. conventional myomectomy - Mohamed Sayed Abd el-Naeem; Abd El-Halim El-Sayed Amin; Amir Ahmed Abdallah; Eisa Mahmoud Mohamed; Kareem Ibrahim Shahin (International Journal of Medical Toxicology and Legal Medicine, 2024)
Myomectomy is a surgical procedure to remove uterine fibroids. It is recommended in symptomatic fibroids or when many results in complications. Those complications may be pelvic pain, heavy menstrual bleeding, pressure symptoms or infertility. Laparoscopic myomectomyis one of the procedures used in management of uterine fibroids. Many studies studied that there were many advantages of laparoscopic myomectomy when compared to conventional myomectomy for treatment of uterine fibroids. However, lack of training in such advanced laparoscopic procedure limits the widespread use of laparoscopic myomectomy. So, the surgeon`s skills in precise enucleation of the myoma and suturing the myoma bed are major deciding factors to perform laparoscopic myomectomy.